MEMAHAMI POLA-POLA KELUAR DARI KEMISKINAN : STUDI KASUS KABUPATEN BOJONEGORO - Achmadi Achmadi; Karjadi Mintaroem; Gigih Prihantono (Jurnal Ekonomi dan Bisnis, 2015)
The study, Moving Out of Poverty: Understanding Freedom, Power, and Democracy, aims to determine which people have successfully moved out of poverty and to examine the process of moving out of poverty in the context of the specific conditions most relevant to the dynamics of socioeconomic mobility in Bojonegoro. The study used an integrated package of qualitative methods in area eksplorasi and non eksplorasi migas. The study found that open stratification, good social capital, functioning local democracy, and improving information infrastructure have helped improve the prosperity of communities.